Concomitant Kinase-Dead BRAF and Oncogenic KRAS Lead to an Aggressive Biologic Behavior and Tumor Lysis Syndrome: A Case Report - Roy Holland; Offir Ben-Ishay; Offir Ben-Ishay; Irit Ben-Aharon; Irit Ben-Aharon; Irit Ben-Aharon (Frontiers in Oncology, 2022)
Tumor lysis syndrome (TLS) is a life-threatening oncological emergency rarely seen in solid tumors and is a complication of cancer therapy for rapidly proliferating tumors with devastating outcomes. BRAF and KRAS are two key oncogenes in the MAPK signaling pathway that are routinely examined for mutations to predict resistance to anti-EGFR therapy. Concomitant KRAS and BRAF mutations in GI tumors are rare, occurring in less than 0.001% of cases and are associated with an aggressive tumor behavior. We report an unusual case of a young male patient diagnosed with locally advanced duodenal mucinous adenocarcinoma harboring concomitant KRAS and BRAF mutations. This unique genetic profile generated hyperactivation of the EGFR signaling pathway. Following day-1 of mFOLFOX-6 chemotherapy protocol, the patient developed TLS. Clinical resolution was achieved using high volume hydration. Unfortunately, the patient passed away 10 days later during anesthesia induction.